Assessment of a consultation-liaison psychiatry and psychology health care program Avaliação do programa assistencial de um serviço de interconsulta psiquiátrica e psicológica - Paola BA Andreoli; Jair de J Mari (Universidade de São Paulo, 2002)
OBJECTIVE: To investigate the relevance of subjective criteria adopted by a psychiatry and psychology consultation-liaison service, and their suitability in the evaluation of case registries and objective results. METHODS: Semi-structured interviews were conducted and all supervisors of the university hospital service were interviewed. Routinely collected case registries were also reviewed. Standardized assessment with content analysis for each category was carried out. RESULTS: The results showed distortions in the adopted service focus (doctor-patient relationship) and consultant requests. This focus is more on consulting physician-oriented interventions than on patients. DISCUSSION: Evaluation of the relevance of service criteria could help promoting quality assessment of the services provided, mainly when objective criteria have not yet been established to assure their suitability. OBJETIVO: Investigar a pertinência dos critérios subjetivos adotados por um serviço de interconsulta psiquiátrica e psicológica e sua adequação na avaliação dos registros e resultados objetivos obtidos. MÉTODOS: Foram realizadas entrevistas semi-estruturadas com todos os supervisores do serviço estudado de um hospital universitário, e revisados os registros de caso coletados rotineiramente no serviço. Foi realizada avaliação formal por meio de análise de conteúdo para cada categoria. RESULTADOS: Os resultados mostram distorção entre o foco adotado pelo serviço (relação médico-paciente) e a demanda dos consultantes. Esse foco direciona para maior predomínio de intervenções direcionadas aos médicos consultantes do que aos pacientes. CONCLUSÃO: A avaliação da pertinência dos critérios adotados pelo serviço pode servir ao propósito de promover análise da qualidade do serviço prestado, principalmente em casos em que não se possuem ainda critérios objetivos que possam atestar sua adequação.